2002
DOI: 10.1667/0033-7587(2002)157[0410:scaxrt]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Skin Cancer after X-Ray Treatment for Scalp Ringworm

Abstract: Some 2,224 children given X-ray therapy for tinea capitis (ringworm of the scalp) have been followed for up to 50 years to determine cancer incidence, along with a control group of 1,380 tinea capitis patients given only topical medications. The study found a relative risk (RR) of 3.6 (95% confidence interval, 2.3-5.9) for basal cell skin cancer (BCC) of the head and neck among irradiated Caucasians (124 irradiated cases and 21 control cases), in response to a scalp dose of about 4.8 Gy. No melanomas of the he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
116
4
2

Year Published

2004
2004
2014
2014

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 141 publications
(137 citation statements)
references
References 31 publications
11
116
4
2
Order By: Relevance
“…This finding is of particular interest given the 10-fold greater background rate of stomach cancer in Japan, and suggests a multiplicative interaction of risks. In a recent report of a study of skin cancer after irradiation in childhood for ringworm of the scalp, Shore et al (2002) confirmed a strong association between basal cell carcinoma and exposure in childhood. However, unlike the findings of Ron et al (1998) for skin cancer in the LSS, Shore et al (2002) suggested that exposure to UVR was important as a cofactor because of the relatively low level of skin cancer among irradiated black patients.…”
Section: Introductionmentioning
confidence: 84%
“…This finding is of particular interest given the 10-fold greater background rate of stomach cancer in Japan, and suggests a multiplicative interaction of risks. In a recent report of a study of skin cancer after irradiation in childhood for ringworm of the scalp, Shore et al (2002) confirmed a strong association between basal cell carcinoma and exposure in childhood. However, unlike the findings of Ron et al (1998) for skin cancer in the LSS, Shore et al (2002) suggested that exposure to UVR was important as a cofactor because of the relatively low level of skin cancer among irradiated black patients.…”
Section: Introductionmentioning
confidence: 84%
“…There is very little evidence in the literature of an increased SCC risk associated with radiation at moderate doses 3,12 and the lack of an association with SCC is consistent with the atomic bomb survivor results 11 and those of medically exposed patients. 7,9,12 Risks associated with total number of years worked present some difficulty in interpretation. Note that by adjusting for year first worked, one may be adjusting for part of the effect of duration of work (or exposure) since those who first worked in earlier years would have had more years of employment than more recent workers.…”
Section: Discussionmentioning
confidence: 99%
“…1 These skin cancers were mostly squamous cell carcinomas (SCCs) and occurred at the site of dermatitis caused by exposure to excessive local doses of ionizing radiation (IR). 2,3 More recent studies of patients irradiated for medical reasons [4][5][6][7][8][9] and Japanese atomic bomb survivors 10,11 have shown an excess risk of skin cancer, particularly basal cell carcinoma (BCC). Medically irradiated patients were mostly exposed to moderately high and fractionated doses of IR early in life.…”
mentioning
confidence: 99%
“…An increased risk of skin cancer associated with exposure to ionizing radiation has been reported in various exposed populations, including the atomic bomb (A-bomb) survivors (1-3), uranium miners (4), radiologists and individuals treated with radiation in childhood for tinea capitis (5,6) and malignant tumors (7,8). The first report among the Abomb survivors in Hiroshima and Nagasaki by the Atomic Bomb Casualty Committee (ABCC) was 26 years after the A-bombs were dropped.…”
Section: Introductionmentioning
confidence: 99%
“…Age at exposure is one of the most significant modifiers of dose response for skin and many other cancers (1,5,7). The LSS subjects who were exposed in childhood have now reached cancer-prone ages.…”
Section: Introductionmentioning
confidence: 99%